2022
DOI: 10.3390/lubricants10080196
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress Regarding the Use of Metal and Metal Oxide Nanoparticles as Lubricant Additives

Abstract: Lubricating oil can effectively reduce friction between mechanical parts, thereby reducing energy consumption and improving service life and reliability. Due to the development of science and technology, it is necessary to improve the performance of lubricating oil to fulfill the higher tribological requirements for countering wear and providing lubrication. Nanolubricant additives have the four lubrication mechanisms of micro-bearing, protective film, polishing, and repair effects. A nanolubricant additive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The protective film effect is the most important lubrication mechanism in which, during the sliding condition of contacting parts, nanoparticles tend to form a layer which is reinforced thoroughly. This significantly reduces friction as there is no direct contact of friction pairs; also, shear strength is reduced and results in antiwear performance. , The polishing effect resulted in reducing the surface roughness of contacting surfaces . As the name clearly depicts, the repair effect of the lubrication mechanism results in filling of cracks or fills by low melting point nanoparticles.…”
Section: Biolubricants: Nature and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The protective film effect is the most important lubrication mechanism in which, during the sliding condition of contacting parts, nanoparticles tend to form a layer which is reinforced thoroughly. This significantly reduces friction as there is no direct contact of friction pairs; also, shear strength is reduced and results in antiwear performance. , The polishing effect resulted in reducing the surface roughness of contacting surfaces . As the name clearly depicts, the repair effect of the lubrication mechanism results in filling of cracks or fills by low melting point nanoparticles.…”
Section: Biolubricants: Nature and Challengesmentioning
confidence: 99%
“…Effectively, there are four effects of the mechanism of lubrication in nano additives, stated as microbearing, protective film, polishing, and repair. 174 The microbearing effect is a situation where the relative sliding friction state is converted into a rolling friction state when nanoparticles enter the contacting area. Spherical and quasi spherical shaped nanoparticles depict such types of effect.…”
Section: Biolubricants: Nature and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zawawi et al [28] analyzed the behavior of the friction coefficient of nano-lubricants composed of Aluminum Oxide and Silicon Oxide (Al 2 O 3 -SiO 2 ), and they concluded that, for a reduction in the friction coefficient of up to 4.78% and an improvement in the wear rate of 12.96%, the optimal volume concentration of nano-lubricants should be 0.02%. It is true that diverse and extensive nanomaterials are used as additives for lubricating oils; however, it is metal nanoparticles or their oxidants and sulfides that have received the most study and research [29,30] because metal nanoparticles enhance the lubricating oil's tribological characteristics through micro-bearing effects and various other mechanisms [31].…”
Section: Introductionmentioning
confidence: 99%
“…Many different metal oxide nanomaterials have been tested as lubricant additives [ 9 , 10 ], but zinc oxide (ZnO) has shown outstanding tribological performance, inducing a lower coefficient of friction and improving wear resistance [ 5 , 11 , 12 ]. In addition to tribological aspects, ZnO nanomaterials have delivered some antioxidant activity, especially acting as radical scavengers that break the propagation step of the lubricating oil oxidation mechanism [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%